2013
DOI: 10.1128/iai.00704-12
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Determinants of Intrinsic Colistin Tolerance in Acinetobacter baumannii

Abstract: bAcinetobacter baumannii is a leading cause of multidrug-resistant infections worldwide. This organism poses a particular challenge due to its ability to acquire resistance to new antibiotics through adaptation or mutation. This study was undertaken to determine the mechanisms governing the adaptability of A. baumannii to the antibiotic colistin. Screening of a transposon mutant library identified over 30 genes involved in inducible colistin resistance in A. baumannii. One of the genes identified was lpsB, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…Acinetobacter spp. have also been shown to acquire mutations in the lipid A biosynthetic pathway when treated with colistin, resulting in resistance to the antibiotic (40)(41)(42)(43). Interestingly, those studies found that mutations in certain lipid A genes resulted in complete loss of LOS.…”
Section: Cell Surfacementioning
confidence: 99%
“…Acinetobacter spp. have also been shown to acquire mutations in the lipid A biosynthetic pathway when treated with colistin, resulting in resistance to the antibiotic (40)(41)(42)(43). Interestingly, those studies found that mutations in certain lipid A genes resulted in complete loss of LOS.…”
Section: Cell Surfacementioning
confidence: 99%
“…All animal experiments were approved by the Vanderbilt University Institutional Animal Care and Use Committee. The murine model of A. baumannii pneumonia was performed as previously described (44)(45)(46)(47)(48)(49). Briefly, Ab17978 bacteria were back-diluted 1:1,000 from an overnight culture and grown for 3.5 h at 37°C with shaking, washed twice with cold phosphate-buffered saline (PBS), and resuspended in PBS at an appropriate cell density for infection.…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were approved by the Vanderbilt University Institutional Animal Care and Use Committee. The murine model of A. baumannii pneumonia was performed as previously described (31)(32)(33)(34)(35)(36). Briefly, A. baumannii ATCC 17978 bacteria were back diluted 1:1,000 from overnight culture and grown for 3.5 h at 37°C with shaking, washed twice with cold PBS, and resuspended in PBS at an appropriate cell density for infection.…”
Section: Methodsmentioning
confidence: 99%